Entrepreneurship, State Economic Development Policy, and the Entrepreneurial University - David B. Audretsch; Ronnie J. Phillips (Max Planck Institute of Economics, 2007)
In this paper, we discuss the nature of the university-industry relationship and recommend specific policies to help achieve the goal of greater economic growth. We argue that state-supported research universities can be used to integrate entrepreneurship into state economic development and incubate entrepreneurial companies. Regional entrepreneurship policy is a new strategy that regards economic development as a process that goes from supporting research and development to creating and growing new businesses. Specifically, we believe that an entrepreneurial higher education system is a key to state-level economic policies. There is an opportunity at research universities to combine the human capital talent available on faculties with the needs and expertise of private industry to accelerate entrepreneurship and economic growth.
Keywords: 330; Wachstumspolitik; Forschungs- und Technologiepolitik; Bildungsinvestition; Hochschulforschung; Unternehmensgründung; USA